The Relationship Between Sports Civic Organizations and Human Resources - Szabados, György Norbert; Bácsné Bába, Éva; Fenyves, Veronika; Bács, Zoltán; Dajnoki, Krisztina; Kovács, Sándor (International Journal of Engineering and Management Sciences, 2019)
Every spring the Hungarian Central Statistical Office records through its ELEKTRA database system the human and economic related operation data of the past year of civic organizations. This data source is usually considered as a standard at the evaluation of the domestic civic sphere. Still, the available handout titled “Most important features of the non-profit sector”, applying mainly descriptive statistics only provides a brief picture of specifications of the sector. Parallel with it, its background database is available yearly, which provides a unique possibility for a researcher to perform secondary analysis aiming to reveal deeper relationship. The objective of our study is purely to reveal a minor part of this considerable field, the relationship between subsidies and human resources mainly due to the fact, that human resource in this sector is composed of employees and volunteers, and it is questionable whether subsidies have an impact on employment.  Results revealed that there is a relationship between human resources and subsidies, where mainly private nature subsidies have a strong impact equally on voluntariness and work related employment